Mapping of Regional Potential and Competitiveness in Constructing a Self-Reliance Model for Mentawai Indigenous Communities - Ardhanari, Margaretha; Sebastianus Widanarto Prijowuntato; Paulus Sukapto; Visi Saujaningati Kristyanto; Marihot Nainggolan (Greenation International Journal of Engineering Science, 2023)
This paper aims to map the potential of the region and competitiveness in constructing a model of self-reliance for the Mentawai indigenous peoples. Design/methodology/approach Techniques of collecting data by interviewing and studying documents and archives. The target respondents are government officials, tribal chiefs, teachers, clergy, and community leaders. Findings - The gross enrollment rate (APK) for elementary schools in 2021 is 115.91 percent; SMP APK is 86.54 percent; and high school APK of 67.07 percent. Practical implications collect data on Mentawai in an effort to build a recommendation namely 1) training for UMA members to determine appropriate training for UMA members, such as services, craft training, food processing, culture, religion, and so on; 2) Recording and enlivening the cultures that exist in UMA; 3) increasing capacity building and developing the character of UMA members, 3) Awareness of tourism potential; 4) Development of internet network and digital literacy. Originality/value this study analyzes a real picture of the Mentawai situation and conditions in an effort to develop so that Mentawai is able to develop in keeping pace with developments with other regions.